Until we find home - Gohlke, Cathy (Tyndale House Publishers, Inc., 2017)
In the early days of WWII, American Claire Stewart smuggles five French Jewish children across the channel before the Nazis storm Paris, and brings them to her estranged aunt's Lake District estate as refugees. Lady Miranda Langford agrees to take them in, but only if Claire stays to help care for them. Though desperate to return to France and the man she loves, Claire agrees, and soon fellow American David Campbell challenges her notions of love. A portrait of life on the British home front, reminding us that bravery and family come in many forms.